The physiological bases of hidden noise-induced hearing loss: protocol for a functional neuroimaging study - Dewey, Rebecca S.; Hall, Deborah A.; Guest, Hannah; Prendergast, Garreth; Plack, Christopher J.; Francis, Susan T. (JMIR Publications, 2018)
Background: Rodent studies indicate that noise exposure can cause permanent damage to synapses between inner hair cells and high-threshold auditory nerve fibers, without permanently altering threshold sensitivity. These demonstrations of what is commonly known as “hidden hearing loss” have been confirmed in several rodent species, but the implications for human hearing are unclear.